Testing of Toxicity of Herbicides Formulated On Non-Target Organisms of Earthworms - Risvan Anwar; Stefanie Juveria; Sarina Sarina; Eka Suzanna; Djatmiko Djatmiko (University of Prof. Dr. Hazairin, SH, 2022)
This study aims to determine the toxicity of the formulated herbicide concentration to non-target organisms (non-target) earthworms. The study was conducted from April to July 2021. The design used was a completely randomized design (CRD) with nine (9) herbicide concentrations (K) treatments, namely: K0 = control, K1 = 200 ppm concentration (0.2 ml/l water ), K2 = concentration of 400 ppm (0.4 ml/ l of water), K3 = concentration of 600 ppm (0.6 ml/ l of water), K4 = concentration of 800 ppm (0.8 ml/ l of water), K5 = concentration 1000 ppm (1.0 ml/ l of water), K6 = concentration of 1200 ppm (1.2 ml/ l of water), K7 = concentration of 1400 ppm (1.4 ml/ l of water), K8 = concentration of 1600 ppm (1, 6 ml/l water). Each treatment was repeated 3 times. The observed variables were mortality concentration 50 (LC50) for 96 hours, survival rate, mortality percentage and worm weight. This study concluded that the mortality concentration of 50 (LC50) for 96 hours from the formulated herbicide against earthworms was 600 ppm, while the 100% mortality occurred at the herbicide concentration of 1400 ppm. The lowest survival rate was found at a concentration of 1400 ppm, where at that concentration all the test worms died. Meanwhile, the highest survival rate after the herbicide was 200 ppm where the worm mortality was 20%. The higher the concentration of herbicide formulation given to earthworms, the higher the mortality rate and decrease in body weight.